LO52: Distraction in the ED using Virtual reality for Intravenous Needs in Children to Improve comfort- DEVINCI - a pilot RCT. (May 2020) - Trottier, E. D.; Osmanlliu, E.; Bailey, B.; Lagacé, M.; Certain, M.; Khadra, C.; Sanchez, M.; Thériault, C.; Paquin, D.; Cotes-Turpin, C.; Le May, S.
Abstract : Introduction: Venipuncture is a frequent cause of pain and distress in the pediatric emergency department (ED). Distraction, which can improve patient experience, remains the most studied psychological intervention. Virtual reality (VR) is a method of immersive distraction that can contribute to the multi-modal management of procedural pain and distress. Methods: The main objectives of this study were to determine the feasibility and acceptability of Virtual Reality (VR) distraction for pain management associated with venipunctures and to examine its preliminary effects on pain and distress in the pediatric ED. Children 7-17 years requiring a venipuncture in the pediatric ED were recruited. Participants were randomized to either a control group (standard care) or intervention group (standard of care + VR). Principal clinical outcome was the mean level of procedural pain, measured by the verbal numerical rating scale (VNRS). Distress was also measured using the Child Fear Scale (CFS) and the Procedure Behavior Check List (PBCL) and memory of pain using the VNRS. Side effects were documented. Results: A total of 63 patients were recruited. Results showed feasibility and acceptability of VR in the PED and overall high satisfaction levels (79% recruitment rate of eligible families, 90% rate of VR game completion, and overall high mean satisfaction levels). There was a significantly higher level of satisfaction among healthcare providers in the intervention group, and 93% of those were willing to use this technology again for the same procedure. Regarding clinical outcomes, no significant difference was observed between groups on procedural pain. Distress evaluated by proxy (10/40 vs 13.2/40, p = 0.007) and memory of pain at 24 hours (2.4 vs 4.2, p = 0.027) were significantly lower in the VR group. Venipuncture was successful on first attempt in 23/31 patients (74%) in the VR group and 15/30 (50%) patients in the control group (p = 0.039). Five of the 31 patients (16%) in the VR group reported side effects Conclusion: The addition of VR to standard care is feasible and acceptable for pain and distress management during venipunctures in the pediatric ED. There was no difference in self-reported procedural pain between groups. Levels of procedural distress and memory of pain at 24 hours were lower in the VR group.